The Delphian prophecy and the fate of the Spartan king Leonidas - Kulishova, Oksana V.; Pechatnova, Larisa G. (Journal of the Belarusian State University. History, 2024)
According to the ancient literary tradition, among the Greek city-states, it was Sparta that was most closely connected with the famous sanctuary and oracle of Apollo in Delphi, not only in a religious, but also in a military-political sense. Tradition has preserved many Delphic prophecies addressed to the Spartan kings, both authentic and composed after the fact. One of them was associated with the name of the Spartan king Leonidas and his participation in the battle of Thermopylae in 480 BC. Perhaps Leonidas himself resorted to the help of the Delphic priests to obtain the prophecy he needed. Herodotus conveys the contents of the Delphic oracle in both prose and poetic form. It is emphasised that modern researchers doubt the authenticity of this prophecy. The subject of discussion is also the circumstances of the origin and various interpretations of the Delphic oracle in ancient sources. It is assumed that different forms of prophecy appeared at different times: the prose form even before the events at Thermopylae, and the poetic form after them. It has been suggested that at least a poetic version of the prophecy appeared after the battle of Thermopylae. It was probably created on the initiative of the royal family of the Agiads, to which Leonidas belonged. It is emphasised that the oracle, according to which the death of its king was declared a condition for the salvation of Sparta, became an integral component of the myth of Leonidas. Using this myth, Sparta successfully transformed the defeat at the battle of Thermopylae into a victory for its political and moral values. The battle of Thermopylae became an important part of the «Spartan mirage», and Leonidas and his squad became a heroic example on which Spartan youth were brought up over the centuries.